PEMBUATAN DAN APLIKASI PUPUK ORGANIK CAIR (POC) SEBAGAI SUBSTITUSI NUTRISI AB MIX TERHADAP TANAMAN KANGKUNG (Ipomoea reptans) PADA HIDROPONIK WICK SYSTEM - Indri Hapsari Fitriyani; Qonita Qurrota A’yun; Gunawan Djajakirana (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
The price of the AB mix is relatively high, so it needed to find another alternative with a more economical price. One of the alternatives is Liquid Organic Fertilizer (LOF). This study aimed to know the quality of LOF made from banana peels and chicken egg shells, the effect of LOF on the water spinach grown in the hydroponic wick system, and the possible use of LOF as a substitute for AB mix. The experiment consisted of three stages. The first stage was the nutrient analysis of raw materials. The second stage was the production of LOF and nutrient analysis. The results of fermented fertilizers are called POC PT. The third stage was an experiment on water spinach in a hydroponic wick system. The experiment used a completely randomized design with five fertilizer treatments, namely P0 (control), P1 (AB mix nutrition), P2 (LOF PT 150%), P3 (LOF PT 100%), P4 (LOF PT 50%) in three replications. The results showed that LOF, which was fermented for three weeks, had a low nutrient content and was below the Ministry of Agriculture standard. The available N content in POC PT was low, so Ca(NO3)2 fertilizer was added to POC PT. The LOF PT treatment had higher plant growth parameter than the control treatment. Thus, the treatment of LOF PT could not substitute AB mix.